Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Jiang, Mou-Yan; Zhou, Yi-Fan; Liu, Hao; Peng, You-Xing; Huang, Yuan-Qing; Deng, Si-Ping; Huang, Yang; Shi, Gang; Zhu, Chun-Hua; Li, Guang-Li; Jiang, Dong-Neng (Frontiers in Marine Science, 2023)
Spotted scat (Scatophagus argus) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus. Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes (fshr, cyp17a1, and foxl2) and insulin-like growth factor pathway genes (igf1r, ifg2r, igfbp1, igfbp3, and igfbp7) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara, ppard, fabp3, and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus.